2009
DOI: 10.1295/polymj.pj2009157
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Assisted Synthesis of Poly(2-hydroxyethyl methacrylate) (HEMA)/Silica Hybrid Using in situ Polymerization Method

Abstract: A facile and fast synthesis of poly(2-hydroxyethyl methacrylate) (PHEMA)/silica hybrid was achieved using in situ polymerization method under microwave irradiation, in which the polymerization of 2-hydroxyethyl methacrylate (HEMA) was carried out together with the sol-gel reaction of methyltrimethoxysilane (MeTMOS). The preparation rate of the hybrid under microwave irradiation was accelerated rapidly relative to that under conventional heating due to the activation of hydroxyl groups of HEMA and silanol group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 22 publications
0
7
0
1
Order By: Relevance
“…We found that simultaneously performing the sol-gel reaction of methyltrimethoxysilane (MeTMOS) using acetic acid and the polymerization of 2-hydroxyethyl methacrylate (HEMA) proceeded rapidly under microwave irradiation. 74 Such a rapid sol-gel reaction enables homogeneous dispersion of robust optical solid materials. In this section, we explain a facile preparation method and the optical properties of boron dipyrromethene (BODIPY) containing polymer-silica hybrid materials.…”
Section: Resultsmentioning
confidence: 99%
“…We found that simultaneously performing the sol-gel reaction of methyltrimethoxysilane (MeTMOS) using acetic acid and the polymerization of 2-hydroxyethyl methacrylate (HEMA) proceeded rapidly under microwave irradiation. 74 Such a rapid sol-gel reaction enables homogeneous dispersion of robust optical solid materials. In this section, we explain a facile preparation method and the optical properties of boron dipyrromethene (BODIPY) containing polymer-silica hybrid materials.…”
Section: Resultsmentioning
confidence: 99%
“…). Methods for step‐growth polymerizations, for example, polycondensation of diols with dicarboxylic acids and polyaddition of dialkynes with diazido via in situ azidation of dibromo compounds, as well as chain polymerizations, for example, radical polymerization of methacrylate, anionic polymerization of acrylamide, ring‐opening cationic polymerization of 2‐oxazoline derivatives, and ring‐opening polymerization (ROP) of cyclic esters, have all incorporated microwave heating. The exponentially increasing number of publications concerning microwave heating of organic reactions indicates the remarkable interest in and effectiveness of this technique …”
Section: Introductionmentioning
confidence: 99%
“…Microwave heating is widely used to accelerate organic reactions, [1][2][3][4][5][6][7][8][9][10][11] to reduce polymerization times, [12][13][14][15] and to enhance the activity of enzymes. [16][17][18] The majority of the reaction acceleration obtained in this manner can be explained by the thermal effect of the microwaves.…”
Section: Introductionmentioning
confidence: 99%